ANALISIS PLACE ATTACHMENT DAN FAMILIARITY TERHADAP DESTINATION LOYALTY PADA PENGUNJUNG PANTAI DI KOTA BATAM - Sihombing, Dame Afrina; Ellysabeth, Ellysabeth; Ariyanto, Hepy Hefri (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This study evaluates how place attachment and familiarity influence destination loyalty among beach visitors in Batam. This research was structured based on a quantitative approach to validate the hypotheses that have been suggested. The target population in this research is tourists who visit beaches in Batam. The data collected is then analyzed using statistical analysis techniques such as the t-test. Based on the test, it was found that 50.2% of the influence exerted on the dependent variable came from the independent variable, while the remaining 49.8% resulted from other factors not included in this research model. The conclusions of this research confirm that place attachment and familiarity significantly influence destination loyalty and can be considered critical elements in retaining tourists in the Batam beach destination. Keywords: Place Attachment; Familiarity; Destination Loyalty